2018
DOI: 10.1097/md.0000000000013080
|View full text |Cite
|
Sign up to set email alerts
|

Biliary tract exploration through a common bile duct incision or left hepatic duct stump in laparoscopic left hemihepatectomy for left side hepatolithiasis: which is better?

Abstract: Laparoscopic left hemihepatectomy (LLH) followed by biliary tract exploration is used to treat left-sided hepatolithiasis (LSH). The purpose of this study was to compare the efficacy of 2 methods of biliary tract exploration in LLH:biliary tract exploration through a common bile duct (CBD) incision (with T-tube drainage) or through the left hepatic duct (LHD) stump (without T-tube drainage).LSH patients (113 patients) were recruited retrospectively in our hospital from December 2008 to January 2016. To compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…2a, Table 2). On the other hand, pooled results for three studies 4,7,8 showed a similar trend in estimated blood loss between LHD and CBD approach (SMD = 0.15; 95% CI: −0.10, 0.41; P = 0.23; Fig. 2b).…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…2a, Table 2). On the other hand, pooled results for three studies 4,7,8 showed a similar trend in estimated blood loss between LHD and CBD approach (SMD = 0.15; 95% CI: −0.10, 0.41; P = 0.23; Fig. 2b).…”
Section: Resultsmentioning
confidence: 63%
“…A total of 849 studies were eliminated following removal of duplicates. The selected 47 articles were subjected to full‐text analysis, resulting in five that were finally included in this meta‐analysis 4,7,8,13,14 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatolithiasis is mainly caused by bacterial infection, parasites, bile stasis, anatomical variation, dietary structure, and genetics, with the pathological changes of hepatobiliary cholestasis, acute and chronic inflammation, inflammatory stenosis, and proximal dilation. [ 14 , 15 ] The accumulating stones in dilated bile ducts could further aggravate the obstruction, leading to repeated inflammation, abscesses, systemic sepsis, and even biliary ulceration. Hepatectomy is the main method to remove stones, correct bile duct stenosis, smooth bile duct drainage, and prevent disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Reported side effects of such tubes include bile loss, infection at the site of the tube, and displacement of the tube. 9 It has been reported that tube drainage after common duct exploration is associated with high-volume biliary output. 6 This patient had excessive bile loss through their tube, and clamping of the tube paired with treatment administration allowed for resolution of the patient's hyponatremia.…”
Section: Discussionmentioning
confidence: 99%